The Effects of Unfermented and Fermented Cow and Sheep Milk on the Gut Microbiota - Rettedal, Elizabeth A.; Altermann, Eric; Roy, Nicole C.; Dalziel, Julie E. (Frontiers in Microbiology, 2019)
A variety of fermented foods have been linked to improved human health, but their impacts on the gut microbiome have not been well characterized. Dairy products are one of the most popular fermented foods and are commonly consumed worldwide. One area we currently lack data on is how the process of fermentation changes the gut microbiota upon digestion. What is even less well characterized are the possible differences between cow and other mammals’ milks. Our aim was to compare the impact of unfermented skim milk and fermented skim milk products (milk/yogurt) originating from two species (cow/sheep) on the gut microbiome using a rat model. Male Sprague-Dawley rats were fed a dairy-free diet supplemented with one of four treatment dairy drinks (cow milk, cow yogurt, sheep milk, sheep yogurt) for 2 weeks. The starter culture bacteria in the yogurts were depleted in this study to reduce their potential influence on gut bacterial communities. At the end of the study, cecal samples were collected and the bacterial community profiles determined via 16S rRNA high-throughput sequencing. Fermentation status drove the composition of the bacterial communities to a greater extent than their animal origin. While overall community alpha diversity did not change among treatment groups, the abundance of a number of taxa differed. The cow milk supplemented diet was distinct, with a higher intragroup variability and a distinctive taxonomic composition. Collinsella aerofaciens was of particularly high abundance (9%) for this group. Taxa such as Firmicutes and Lactobacillus were found in higher abundance in communities of rats fed with milk, while Proteobacteria, Bacteroidetes, and Parabacteroides were higher in yogurt fed rats. Collinsella was also found to be of higher abundance in both milk (vs. yogurt) and cows (vs. sheep). The results from this study show that fermentation of dairy products had the greatest impact on gut bacterial communities, while the animal species of origin had a lesser influence. This research adds to our understanding on how food consumption may alter the gut microbiome and could be used to help determine how we can maintain or directionally rebalance it to an optimal state.